Vascularized Iliac Crest Bone Graft for the Reconstruction of Anterior Vertebral Corpus Defects: A Literature Review and Cadaveric Feasibility Study - Jonathan L. Jeger, MB BCh; Casey J. Martinez, BS; Maria Shvedova, MD; Alec Simoni, BS; Alanna Rebecca, MD; Sebastian Winocour, MD; Alexander E. Ropper, MD; Michael Bohl, MD; William J. Casey, III, MD; Maziyar Kalani, MD; Edward M. Reece, MD, MS (Plastic and Reconstructive Surgery, Global Open)
Background:. Vertebral body defects pose a significant challenge in spinal reconstructive surgery. Compression fractures of the vertebral corpus are typically treated with vertebral augmentation procedures. There are significant risks associated with the introduction of foreign material in the spine, including infection and pseudarthrosis. Vascularized bone grafts (VBGs) have become a popular alternative for spinal reconstruction in the last decade thanks to their robust blood supply and autologous nature. VBGs have been described predominantly for the reconstruction of posterior vertebral defects. The objective of this study is to describe a novel procedure for the reconstruction of vertebral corpus defects in the lumbar and distal thoracic spine. Methods:. This is a cadaveric anatomy study. The authors performed the novel surgical technique on an anonymized cadaveric donor in the prone position and recorded the procedure through clinical photography. Consent for the procedure and photography was obtained from the Center for Procedural Innovation. Results:. A 5-cm-long posterior iliac crest VBG (IC-VBG) was successfully harvested on a pedicle of the quadratus lumborum muscle. The VBG was rotated and mobilized anteromedially to the vertebral corpus. In this donor, the IC-VBG could be inset with minimal tension anywhere along the vertebral bodies of the spine from the L5 to the T9 level. Conclusions:. A rotated, anteromedially mobilized IC-VBG represents a novel technique for reconstruction of the anterior vertebral corpus of the lumbar and distal thoracic spine with a lower risk of infection and pseudarthrosis than reconstruction with foreign materials.